P102: Education and training on mild traumatic brain injury among emergency department physicians: a systematic review. (15th May 2017) - Patrick, S.; Gaudet, L.; Krebs, L.; Chambers, T.; Rowe, B.H.
Abstract : Introduction: Mild traumatic brain injury (mTBI) is the most common emergency department (ED) brain injury presentation in Canada; however, an evidence-practice gap in mTBI management exists among ED physicians, evidenced by significant practice variation. This review aimed to identify mTBI education and training directed at ED physicians and its relationship with practice patterns and physician knowledge.Methods: A comprehensive literature search of four bibliographic databases and the grey literature was performed using the keywords: concussion, mTBI, medical education, and continuing medical education. Included studies were required to report on mTBI education received by practicing ED physicians. Two independent reviewers screened unique citations for relevance and reviewed the full-texts of relevant articles. Two independent reviewers assessed methodological quality using the Methodological Index for Non-Randomized Studies. Data were extracted in duplicated onto standardized forms. Throughout the review process, discrepancies were adjudicated by an independent third party.Results: A total of 409 unique results were retrieved, and five studies were included. None of the included studies were of high methodological quality. Included studies assessed mTBI educational toolkits (n=3), conference presentations and academic journal articles (n=1), and pediatric fellowship training (n=1). Training primarily occurred after residency (i.e., continuing professional development) and focused on awareness and management of mTBI. Three studies measured ED physicians self-reported knowledge uptake and retention, and all three studies reported positive changes in knowledge uptake including self-reported increases in appropriate return-to-school and return-to-play recommendations. An increase in appropriate return-to-school/sports recommendations was reported in one study, measured by surveying parents of children diagnosed with mTBI.Conclusion: After a systematic and comprehensive search, few studies on mTBI education or training targeting ED physicians were identified and focused on process change rather than outcomes, highlighting an evidence-practice gap that needs to be addressed to improve mTBI patient care. Existing mTBI knowledge translation, including EDP education, needs to be optimized to effectively disseminate evidence-based best-practices for mTBI management in the ED.